Predation Power of Sepat Fish (Trichogaster Trichopterus) and Tilapia(Oreochromis Niloticus) Against Mosquito Larva As a Vector Control - Melinda Kania Listiani; Ema Mayasari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2022)
Vector-borne diseases that are still a public health problem in Indonesia are dengue fever, malaria and filariasis. Utilization of fish as natural predators of mosquito larvae such as sepat fish (Trichogaster trichopterus) and tilapia (Oreochromis niloticus) is one way of biological control that is easy for the community to do. This study aims to determine the predation power of sepat fish (Trichogaster trichopterus) and tilapia (Oreochromis niloticus) against mosquito larvae as an effort to control vectors. This type of research is experimental using the One shoot case study design. The variables of this study were 9 mosquito larvae, sepat fish (Trichogaster trichopterus) and tilapia (Oreochromis niloticus) each. Each time the observation used 100 mosquito larvae and was carried out 9 repetitions. Observations were made for 1, 2, 4 and 6 hours. Data analysis used the Independent Samples Test. The results of the Independent Samples Test obtained a p value of 0.000, proving that there is a difference between the predation power of sepat fish (Trichogaster trichopterus) and tilapia (Oreochromis niloticus) against mosquito larvae. According to this study, the best predatory fish is tilapia (Oreochromis niloticus).It is recommended that the public use predatory fish in an effort to control diseases caused by mosquitoes